About the economic equivalent of reactive power of electric supply systems - Дорошенко, Олександр Іванович (Technology audit and production reserves, 2014)
A scientific and methodological approach to assess the economic costs of electricity consumers from their own reactive load power supply systems, based on an understanding of electricity as a physical phenomenon is proposed. In this case: 1. a working tool of this system is its electromagnetic field that creates the simultaneous action of voltage and conduction current of conducting part of system on electro-elastic dielectric environment surrounding the mentioned parts. 2. Reactive power of system is its internal energy and it isn’t physically transferred to consumers or from them. By regulation definition, such economic losses of consumers are provided if the standard value of economic equivalent of reactive power, the same for all consumers, depending on the number of transformations in their supply network, is kept in systems of its supply. This position is not supported by either physically or mathematically. Therefore, there is no single point of view on the use of such factors in the specialized electric energy literature. In this article there are proposed the determination of economical coefficient of reactive supply based on real mathematical model of electric supply system and there are given the technique of its determination for real system. In this case, the consumer’s loss from its reactive load in cash is determined. This technique can uniquely determine the problem: pay for not existing reactive power by suppliers, or buy the compensate devices of their own reactive load.